Disability and difference in global contexts: enabling a transformative body politic - Erevelles, Nirmala (Palgrave Macmillan, 2011)
« This book explores the possibilities and limitations re-theorizing disability using historical materialism in the interdisciplinary contexts of social theory, cultural studies, social and education policy, feminist ethics, and theories of citizenship. »-- Résumé de l'éditeur.
Keywords: EDI; approches et analyses; capacitisme; corps; cours; discipline; pol4212; premier cycle; santé; systèmes d'oppressions; thématiques; études critiques du handicap